ATYPICAL FATHERHOOD AND BEHAVIOR ANALYSIS: THE POWER OF THE FATHER AS AN AGENT OF TRANSFORMATION IN ASD - Narthagnan Chaves da Silva, Francisco (Health and Society, 2025)
This essay explores fatherhood in the context of Autism Spectrum Disorder (ASD), addressing the painful duality between the statistics of paternal abandonment and the extraordinary power of the father who remains and actively engages. It argues that paternal presence, when informed by the principles of Applied Behavior Analysis (ABA) and exercised in the natural environment of the home, transcends mere support to become one of the most effective forms of therapeutic intervention. Grounded in the literature and intertwined with the author’s personal account—a father who discovered his own ASD diagnosis while seeking help for his children—the text argues that the father’s conscious involvement is a critical variable that catalyzes development, strengthens the family bond, and redefines the meaning of fatherhood itself.